Teaching Essay in Nigeria from the Examiner’s Perspectives - Nwaiwu, Mishael C; Nnanna, Ngozi R (Mediterranean Journal of Social Sciences, 2011)
The variance between teachers’ approach to essay writing and the examiners’ expectation has greatly affected theperformance of the candidates. This is because the candidates go to examination in search of expository, argumentative,narrative, descriptive essays and others, while the examiner marks them on content, organization, expression and mechanicalaccuracy. This paper calls on the teachers of English to teach the candidates according to the expectations of the examiners,especially on how to effectively use the styles of expository, argumentative, narrative, descriptive and others, to explicate thecontent, organization, expression and mechanical accuracy as required by the examiners in essay writing.